Association of basketball season with body composition in elite junior players - Santos, D. A.; Matias, C. N.; Rocha, P. M.; Minderico,C. S.; Allison, D. B.; Sardinha, L. B.; Silva, A. M. (The Journal of Sports Medicine and Physical Fitness, 2014)
Aim: Body composition changes among elite athletes may influence competitive performance. This study aimed to characterize the body composition changes at the molecular, cellular, tissue, and whole-body level of analysis in elite junior basketball players during the course of a season. Methods: Twelve males and 11 females (16 to 17 years) were evaluated. Dual-energy X-ray absorptiometry (DXA) was used to assess bone mineral (Mo) and lean-soft tissue (LST). Total-body water (TBW) and extracellular water (ECW) were assessed using isotope dilution techniques, and extracellular (ECF) and intracellular fluids (ICF) were calculated. Fat mass (FM) and fat-free mass (FFM) were assessed with a four-compartment model. Body cell mass was calculated (LST - (ECF + ECS)). Skeletal muscle (SM) was estimated using appendicular LST (ALST) as: (1.19 x ALST) - 1.65. At the whole-body level, weight, sum of 7 skinfolds, and muscle circumferences (Mc) were measured. The handgrip and the countermovement jump tests were used for performance assessment. Results: Males increased FFM (4.4±2.3%), TBW (3.5±4.6%), SM (4.5±2.3%), and arm (3.4±2.7%) and thigh (3.8±3%) Mc. Females increased SM (5.9±4.6%) and arm (3.6±3.8%) and thigh (4±5.2%) Mc and decreased ICF (-9.7±13.6%). FFM components differed from the established values based on cadaver analysis. Both genders increased their performance and associations were found between changes in molecular and whole-body components with performance. Conclusion: In conclusion the season was associated with an improved body composition profile in males and few changes in females.